What do we know about non-epileptic seizures in adults with intellectual disability: A narrative review. (October 2021) - Rawlings, Gregg H.; Novakova, Barbora; Beail, Nigel; Reuber, Markus
Highlights: People with an ID are an important subgroup of the PNES patient population. A median rate of 9.4% of comorbid ID was found across eleven PNES cohorts. Clinical differences in PNES were found between adults with and without ID. There is heterogeneity in PNES, even within subgroups of the larger population. There is limited evidence examining PNES in adults with ID. Abstract: Psychogenic non-epileptic seizures (PNES) superficially resemble epileptic seizures, but are not associated with abnormal electrical activity in the brain. PNES are a heterogeneous entity and while there is increasing interest in the characterisation of PNES sub-groups, little is known about individuals with PNES who have an intellectual disability (ID). ID is a lifelong condition characterised by significant limitations in cognitive, social and practical skills. ID (commonly with comorbid epilepsy) has been identified as a risk factor for developing PNES. However, people with ID are often excluded from research in PNES. This has unfortunately resulted in a lack of evidence to help inform practice and policy for this population. This narrative review synthesises the currently available evidence in terms of the epidemiology, demographic and clinical profile of adults with PNES and ID. There is a particular focus on demographics, aetiological factors, PNES characteristics, diagnosis and treatment of the condition in this population. Throughout this article, we critique the existing evidence, discuss implications for clinical practice and highlight the need for further research and enquiry. What emerges from the evidence is that, even within the sub-group of those with ID, PNES are a heterogeneous condition. Individuals with ID and PNES are likely to present with diverse and complex needs requiring multidisciplinary care. This review is aimed at the broad range of healthcare professionals who may encounter this group. We hope that it will stimulate further discussion and research initiatives.